Surgical treatment of multiple intracranial aneurysms - Nelson Martelli; Benedicto Oscar Colli; João Alberto Assirati Jr; Hélio Rubens Machado; Roberto Parente Jr (Arquivos de Neuro-Psiquiatria)
A retrospective study was conducted on 42 patients with multiple aneurysms surgically treated from 1975 to 1986. Thirty one of them had 2 aneurysms 6 had 3, 3 had 4 and 2 had 5 (62 in the internal carotid, 27 in the middle cerebral artery, 11 in the anterior cerebral and 3 in the basilar artery). All patients had subarachnoid hemorrhage and were classified as follows upon admission: 11, grade I; 12, grade II; 15, grade III, and 4, grade IV, and most of them improved before surgery (29, grade I, 7, grade II, and 6, grade III). In most cases, surgery was delayed and the 42 patients needed 57 craniotomies for clipping the aneurysms. Of the 24 patients with bilateral aneurysms, 15 were operated on both sides (11 are asymptomatic, 1 has hemiparesis, and 3 died later). Of the 9 patients submitted to unilateral craniotomy, 4 died and 5 are alive and well. Of the 18 patients with unilateral aneurysms, 11 are asymptomatic, 2 have hemiparesis, 1 has diplegia and behavioral disorders, and 4 died. Overall mortality was 26.1%, intraoperative mortality was 11.9%, and no mortality occurred among the patients operated over the last 5 years. The management of the these patients is discussed.